VARIATION OF THE TEMPORAL CO2, ACCUMULATED CO2 EMISSION AND IMPROVEMENT OF CHARACTERISTICS ASSOCIATED WITH THE FERTILITY OF AN ACID SOIL THROUGH THE APPLICATION OF BIOCHAR - RUPAY, Jannet (2023)
Traditionally, to correct the acidity of soil, lime or agricultural dolomite is used, these conventional liming agents can bring as a secondary effect the decrease in soil organic matter (SOM), the carbon stock and the emission of greenhouse gases (GHG). Alkaline biochar is an alternative due to its stability and ability to obtain a positive carbon balance, improve agricultural soils and generate lower GHG emissions. We evaluated the CO2 emission and the physical and chemical properties of acid soil when amended with biochar, lime, and agricultural dolomite in a greenhouse. versus a control (without amendment). Without cultivation, agricultural lime and biochar had a rapid reaction raising the pH close to 7; biochar increased the content of organic matter (+23%), nitrogen (+20%), available phosphorus (+116%), CEC (+46%) and exchangeable cations. Temporal CO2 emission within 24 hours increased with biochar (131%) and dolomite (+41%), although it decreased significantly afterward. On the other hand, with the maize crop, the biochar maintained the desired pH value, and available phosphorus (+109%) and potassium (+224%), CEC (+6%) and exchangeable cations were higher; the temporary emission within 24 hours was higher for biochar (+314%), lime (+115%) and dolomite (+112%); and for the accumulated CO2, biochar presented the highest value (+53%). At day 56, CO2 emissions were not significantly different from the control for the three amendments, and even lower from day 75, which would mean a reduction in long-term emissions.